A constituição da escola activa e a formação de professores no Espírito Santo (1928-1930) - Berto, Rosianny Campos (2013)
The research historically analyzes the active school constitution process in the State of Espírito Santo, in the context of the public instruction reform in the State proposed by Attilio Vivacqua, Instruction secretary, between 1928 and 1930. It aims at searching for strategies that configure the teachers formation process as key element of the New School reform in Espírito Santo, taking the Rehearse Active School and the Course of Pedagogical Culture as irradiator centers of the “new” in Espírito Santo education, inspired by the New School precepts and, more specifically, by the active school in circulation in Brazil and all over the world. The documental corpus is constituted of government messages, reports of the Instruction Secretariat, articles published in local, national and international periodic (News, official and pedagogical), inspection reports, laws and decrees, bibliographic sources and images. For the document analysis, it is advised by the propositions of Ginzburg (1987, 2002, 2003, 2007), through the comprehension of the historiography as tapestry and searching for force relations that can permeate the production of sources and for an understanding that goes beyond the text. The work dialogues with the past/present relations regarding Bloch (2001) and with notions of strategy and tactics, Certeau (2004), in order to think the questions that involve: dialogues with the local and national academic productions about the reforms based on the active school precepts; interlocutions with other renovation movements, in other social ambits, in local and national scenes; configuration elements and the rigging of the instruction reform in Espírito Santo; formation of teachers within scientific principles and strategies to circulate ideas of the reform by the State of Espírito Santo, by the hands of the school inspectors or by the disclosure of the ideas through the press. It considers that the active school constitution in Espírito Santo was processed in nets weaved by the subjects who used to think about education and the reform in the State, owing to the articulation with the modernization ideas going on in national and international ambits. This research was developed among the tensions between the new and the old, nationalist wishes and Brazilianness feelings, at the same time when it was strongly dialogued with scientific precepts in a way to orientate, as the reform engine, process of teachers formation that could enable to propagate the active school ideas inside the Espírito Santo schools, what had as obstacles some economic issues and poor conditions to work as teachers in most of the schools in Espírito Santo.